The contribution of developmental experience vs. condition to life history, trait variation and individual differences. (24th March 2016) - DiRienzo, Nicholas; Montiglio, Pierre‐Olivier
Summary: 1. Developmental experience, for example food abundance during juvenile stages, is known to affect life history and behaviour. However, the life history and behavioural consequences of developmental experience have rarely been studied in concert. As a result, it is still unclear whether developmental experience affects behaviour through changes in life history, or independently of it. 2. The effect of developmental experience on life history and behaviour may also be masked or affected by individual condition during adulthood. Thus, it is critical to tease apart the effects of developmental experience and current individual condition on life history and behaviour. 3. In this study, we manipulated food abundance during development in the western black widow spider, Latrodectus hesperus, by rearing spiders on either a restricted or ad lib diet. We separated developmental from condition‐dependent effects by assaying adult foraging behaviour (tendency to attack prey and to stay on out of the refuge following an attack) and web structure multiple times under different levels of satiation following different developmental treatments. 4. Spiders reared under food restriction matured slower and at a smaller size than spiders reared in ad lib conditions. Spiders reared on a restricted diet were more aggressive towards prey and built webs structured for prey capture, while spiders reared on an ad lib diet were less aggressive and built safer webs. Developmental treatment affected which traits were plastic as adults: restricted spiders built safer webs when their adult condition increased, while ad lib spiders reduced their aggression when their adult condition increased. The amount of individual variation in behaviour and web structure varied with developmental treatment. Spiders reared on a restricted diet exhibited consistent variation in all aspects of foraging behaviour and web structure, while spiders reared on an ad lib diet exhibited consistent individual variation in aggression and web weight only. 5. Developmental experience affected the average life history, behaviour and web structure of spiders, but also shaped the amount of phenotypic variation observed among individuals. Surprisingly, developmental experience also determined the particular way in which individuals plastically adjusted their behaviour and web structure to changes in adult condition. Abstract : The authors' findings demonstrate large and persistent effects of juvenile experience on later adult behavioural phenotype and web structure in black widow spiders. These differences in experience resulted in different patterns of behaviour and web personality in adult spiders. Furthermore, developmental experience also affects which traits demonstrated plasticity as adults.